Bilberry pomace in growing rabbit diets: effects on quality traits of hind leg meat. Issue 3 (3rd July 2017) - Dabbou, Sihem; Renna, Manuela; Lussiana, Carola; Gai, Francesco; Rotolo, Luca; Kovitvadhi, Attawit; Brugiapaglia, Alberto; Helal, Ahmed Noureddine; Schiavone, Achille; Zoccarato, Ivo; Gasco, Laura
Abstract: The aim of the present study was to evaluate the effects of dietary bilberry pomace (BP) on colour, cooking losses, proximate composition and fatty acid (FA) profile of hind leg meat in growing rabbits. One hundred and forty-four Grimaud weaned rabbits (35 days old) were randomly divided into four groups of 36 animals each and fed ad libitum with a basal diet (C diet) tested against three assay diets developed by substituting 50, 100 and 150 g/kg of the C diet with BP (BP5, BP10 and BP15 diets, respectively). At 83 days of age, the rabbits were slaughtered without fasting. Inclusion of BP in the diet did not significantly affect colour, cooking losses, ash and protein contents, but determined a significant increase of ether extract in the muscle. Increasing dietary inclusion of BP also determined a proportional increase of total polyunsaturated fatty acids (PUFA) and total n-3 FA, as well as a proportional decrease of total saturated fatty acids (SFA), total branched chain fatty acids (BCFA) and total monounsaturated fatty acids (MUFA) in the muscle. Dietary BP significantly improved the PUFA/SFA ratio, the Σ n-6/Σ n-3 FA ratio and the atherogenicity, thrombogenicity and hypocholesterolemic/hypercholesterolemic FA indexes of rabbit meat but it decreased Δ5-desaturase plus Δ6-desaturase index. The obtained results suggest that BP inclusion in growing rabbit diets can improve the fatty acid profile of hind leg meat, with consequent health benefits to consumers.